Besifloxacin: A Critical Review of Its Characteristics, Properties, and Analytical Methods - Tótoli, Eliane Gandolpho [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Taylor & Francis, 2018)
Bacterial conjunctivitis has high impact on the health of the population, since it represents more than a third of ocular pathologies reported by health services worldwide. There is a high incidence of bacterial resistance to the antimicrobials most commonly used for the treatment of conjunctivitis. In this context, besifloxacin stands out, since it is a fluoroquinolone developed exclusively for topical ophthalmic use, presenting a low risk of developing resistance due to its reduced systemic exposure. Bausch & Lomb markets it as ophthalmic suspension, under the trade name Besivance™. Literature review on besifloxacin is presented, covering its pharmaceutical and clinical characteristics, and the analytical methods used to measure the drug in pharmaceutical products and biological samples. High performance liquid chromatography is the most used method for this purpose. A discussion on Green Chemistry is also presented, focusing the importance of the development of green analytical methods for the analysis of drugs.
Keywords: Analytical methods; besifloxacin; fluoroquinolones; green analytical chemistry; quality control